Energy Efficient Secure Communication Over Decode-and-Forward Relay Channels - Wang, Dong; Bai, Bo; Chen, Wei; Han, Zhu (IEEE transactions on communications, 2015)
In this paper, we raise the concern on energy-efficient secure communication over a decode-and-forward relay network with potential eavesdroppers. Our objective is maximizing the secure energy efficiency (EE), which is defined as the ratio of secrecy rate to total power, subject to the given individual power, relay decoding rate, and target secrecy rate constraints. The problem is formulated as a unified mixed integer nonlinear optimization adapting to different assumptions of channel state information (CSI). To deal with this combinatorial optimization, a suboptimal solution scheme is developed upon some mathematical methods as decoupling of mixed integer programming, fractional programming, dual decomposition, and difference of convex functions programming. The core of the scheme is to transform the primal problem into simple subproblems step by step, and then convex programming can be exploited finally. The proposed scheme for the case with statistical eavesdropper's CSI, may be conditionally extended to the scenario with full CSI in which a local optimal solution may be obtained in certain cases. Finally, the performance and achievable secure EE of the proposed algorithm are demonstrated by simulations where the tradeoff between secure EE and secrecy rate is also revealed.